Total synthesis of sinopyrine B. (14th September 2022) - Li, Jing; Jiang, Li-Ming; Cheng, Fu; Zhou, Yu-Jia; Duan, Dong-Sen; Zhu, Dao-Yong; Zhang, Kun; Xiong, Zhuang; Wang, Shao-Hua
Graphical abstract: The first total synthesis of sinopyrine B has been concisely achieved in 10 linear steps with a 7% overall yield. Importantly, the crucial pyrrolo[2, 1- a ]isoquinoline skeleton, widely existing in various natural products and pharmacological molecules, was rapidly constructed in one step through a unique formal [3 + 2] cyclization between 2-(3, 4-dihydroisoquinolin-2(1 H )-yl)malononitrile 3 and trimethyl silyl acetylene as the key step. Abstract: The first total synthesis of sinopyrine B has been concisely achieved in 10 linear steps with a 7 % overall yield. Importantly, the crucial pyrrolo[2, 1- a ]isoquinoline skeleton, widely existing in various natural products and pharmacological molecules, was rapidly constructed in one step through a unique formal [3 + 2] cyclization between 2-(3, 4-dihydroisoquinolin-2(1 H )-yl)malononitrile 3 and trimethyl silyl acetylene as the key step.